2023
DOI: 10.3390/ph16020165
|View full text |Cite
|
Sign up to set email alerts
|

EPHB4-RASA1-Mediated Negative Regulation of Ras-MAPK Signaling in the Vasculature: Implications for the Treatment of EPHB4- and RASA1-Related Vascular Anomalies in Humans

Abstract: Ephrin receptors constitute a large family of receptor tyrosine kinases in mammals that through interaction with cell surface-anchored ephrin ligands regulate multiple different cellular responses in numerous cell types and tissues. In the cardiovascular system, studies performed in vitro and in vivo have pointed to a critical role for Ephrin receptor B4 (EPHB4) as a regulator of blood and lymphatic vascular development and function. However, in this role, EPHB4 appears to act not as a classical growth factor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 72 publications
4
7
0
Order By: Relevance
“…The finding that EC synthesis of collagen IV alpha 1 is mostly confined to embryonic development is consistent with and provides at least part of an explanation for the temporally-restricted blood vascular phenotypes of mice induced to express mutant collagen IV alpha 1 or to lose expression of RASA1 or EPHB4 (Alavi et al, 2016;Chen et al, 2019Chen et al, , 2022Chen et al, , 2023Jeanne et al, 2015;Jeanne & Gould, 2017;Kuo et al, 2012;Lapinski et al, 2012Lapinski et al, , 2017van Agtmael et al, 2010). In addition, findings provide a basis for the occurrence of vascular lesions at birth or in early childhood in most patients with inherited mutations in COL4A1, COL4A2, RASA1 and EPHB4 genes (Amyere et al, 2017;Jeanne & Gould, 2017;Kuo et al, 2012;Revencu et al, 2013).…”
supporting
confidence: 61%
See 4 more Smart Citations
“…The finding that EC synthesis of collagen IV alpha 1 is mostly confined to embryonic development is consistent with and provides at least part of an explanation for the temporally-restricted blood vascular phenotypes of mice induced to express mutant collagen IV alpha 1 or to lose expression of RASA1 or EPHB4 (Alavi et al, 2016;Chen et al, 2019Chen et al, , 2022Chen et al, , 2023Jeanne et al, 2015;Jeanne & Gould, 2017;Kuo et al, 2012;Lapinski et al, 2012Lapinski et al, , 2017van Agtmael et al, 2010). In addition, findings provide a basis for the occurrence of vascular lesions at birth or in early childhood in most patients with inherited mutations in COL4A1, COL4A2, RASA1 and EPHB4 genes (Amyere et al, 2017;Jeanne & Gould, 2017;Kuo et al, 2012;Revencu et al, 2013).…”
supporting
confidence: 61%
“…CM-AVM is an autosomal dominant disorder caused by inactivating mutations of RASA1 that encodes the RASA1 Ras GTPase-activating protein (CM-AVM1) or the Ephrin receptor B4 (EPHB4) growth factor receptor tyrosine kinase (CM-AVM2) (Amyere et al, 2017;Eerola et al, 2003;Revencu et al, 2013). Studies of conditional RASA1-and EPHB4-deficient mice have revealed that in EC, RASA1 and EPHB4 act together to limit activation of the Ras-mitogen active protein kinase (MAPK) signaling pathway (Chen et al, 2019(Chen et al, , 2022(Chen et al, , 2023.…”
mentioning
confidence: 99%
See 3 more Smart Citations